Primary teaching in Lithuanian official school in the second hall of the 19th century - Karčiauskienė , M. (Psichologija, 1969)
Primary teaching aims, content and methods applied in the official primary school of Lithuania in the second half of the 19th century are dealt with in the article. A special stress is laid on the one-class people’s school formed according to the 1863 Charter. The reactionary trend of the school is pointed out and the struggle of local people for improving people’s education in Lithuania in shown.